Age and origin of coeval TTG, I- and S-type granites in the Famatinian belt of NW Argentina - Pankhurst, Robert (2000)
Three granitoid types are recognised in the Famatinian magmatic belt of NW Argentina, based on lithology and new geochemical data: (a) A minor trondhjemite-tonalite- granodiorite (TTG) group, (b) a metaluminous I-type gabbro-monzogranite suite, and (c) S-type granites. The latter occur as small cordieritic intrusions associated with I-type granodiorites and as abundant cordierite-bearing facies in large batholithic masses. Twelve new SHRIMP U-Pb zircon ages establish the contemporaneity of all three types in Early Ordovician times (mainly 470- 490 Ma ago). Sr- and Nd-isotopic data suggest that, apart from some TTG plutons of asthenospheric origin, the remaining magmas were derived from a Proterozoic crust-lithospheric mantle section. Trace element modelling suggests that the TTG originated by variable melting of a depleted gabbroid source at 10-12 kbar, and the I-type tonalite-granodiorite suite by melting of a more enriched lithospheric source at c. 5 kbar. The voluminous intermediate and acidic I-types involved hybridisation with lower and middle crustal melts. The highly peraluminous S-type granites have isotopic and inherited zircon patterns similar to those of Cambrian supracrustal metasedimentary rocks deposited in the Pampean cycle, and were derived from them by local anatexis. Other major components of the S-type batholiths involved melting of deep crust and mixing with the I-type magmas, leading to an isotopic and geochemical continuum.